Screening of Auxin-Producing Bacteria from Several Crops Rhizospheres - Prasetyo, Vandi Putranto; Hazmi, Muhammad; Murtiyaningsih, Hidayah (Universitas Muhammadiyah Jember, 2024)
Plants have natural compounds that can stimulate plant growth and development called phytohormones. Phytohormones can be produced endogenously by plants themselves and are not optimal. Therefore it requires exogenous phytohormones that come from outside the plant. In some cases, non-pathogenic bacteria can promote plant growth and be used in agriculture as biofertilizers. Soil rhizospheres from crops are suspected that the soil in the root area (rhizosphere) contains bacteria that stimulate plant growth. Hormones that play a role in plant growth function in division, enlargement of sprout cells, and division of cells at the root growth point. This research aims to determine bacteria that potentially produce the hormone auxin. This research identifies bacterial isolates from microscopic and macroscopic characterization. Screening isolates of auxin-producing bacteria using colorimetric methods and spectrophotometric methods. The results of characterization and screening from 5 samples showed that the bacterial samples that had the potential to produce auxin were samples isolated from eggplant soil (e) with a concentration of 6.5 ppm. The auxin produced is auxin IBA (Indole-3-butyric acid). The IBA auxin content is high enough to be applied as a plant growth-promoting bacteria.